Results of urgent thrombolysis in patients with major stroke and atherothrombotic occlusion of the cervical internal carotid artery. - Endo, S; Kuwayama, N; Hirashima, Y; Akai, T; Nishijima, M; Takaku, A (American Journal of Neuroradiology, 1998)
PURPOSE Atherothrombotic occlusion of the cervical internal carotid artery (ICA) without collateral flow is one of the most critical forms of acute ischemia. We report the results of urgent thrombolytic treatment of patients with major stroke in this clinical category.METHODS Clinical findings and outcome in 33 patients were investigated. All patients had suffered a major stroke, with a score of 24 or higher on the NIH Stroke Scale on admission. Ischemic abnormalities were not detected on initial CT studies. Diagnoses were made at angiography, and patients were treated by intravenous or intraarterial local thrombolysis within 6 hours of stroke onset.RESULTS Recanalization was accomplished in eight patients with intraarterial local thrombolysis; four of these patients had a good clinical outcome. Two factors characteristic of those whose treatment was successful were dramatic improvement of symptoms after partial recanalization achieved within 3 hours of onset and stabilized improvement after subsequent percutaneous transluminal angioplasty or carotid endarterectomy for residual atherosclerotic stenosis at the ICA origin.CONCLUSION The results of this study suggest that urgent intraarterial local thrombolysis may be a successful treatment method for some patients in this critical clinical category if the treatment can be accomplished within 3 hours of ictus and followed by either angioplasty or endarterectomy for residual stenosis.